The dominance of mechanistic behaviour: a critical study of emergency exercises. (1st January 2013) - Berlin, Johan M.; Carlström, Eric D.
In this paper, the focus is on emergency exercises between the police, rescue services and ambulance. By practising, it is assumed that the conditions improve for a quick normalisation after an incident. The purpose of this paper is to identify whether the exercises are designed after organic action logic and therefore can be assumed to strengthen the ability to handle emergencies. Data have been collected at two large, regional, full-scale exercises (2008 and 2012). Data collection has been done through observations and document studies. The study shows that mechanistic behaviour is quite prevalent in the two studied exercises. They are time consuming and put little emphasis on practising organic behaviour. Too complex exercise scenarios contribute to a low tempo, long waiting periods and slow implementation. To succeed, the exercises need to have a non-linear time sequence and limited scenarios that invite participants to focus on organisational interfaces.